PSYCHOLOGICAL TREATMENT VARIANT WITH EYE MOVEMENT DESENSITIZATION AND REPROCESSING: A CASE REPORT - Checa, Alejandro (MNJ (Malang Neurology Journal) (Online), 2023)
Background: EMDR (eye movement desensitization and reprocessing) is a structured psychotherapy method that facilitates the treatment of various psychopathologies and problems related to both traumatic events and more common but emotionally stressful experiences.1 Due to the confinement due to the COVID-19 (Coronavirus Disease 2019) pandemic, people have developed a mixture of anticipatory anxiety, stress, tiredness, misunderstanding and fear, a psychological and emotional mixture that does not fit into any of the existing boxes in the classification of mental disorders.2 Eye Movement Desensitization and Reprocessing (EMDR) has abundant evidence of efficacy in trauma spectrum disorders. Its efficacy in anxious and depressive disorders in children and adolescents has been scarcely studied.3 Objective: To evaluate the efficacy of an alternative EMDR protocol. Methods: It is about a 13-year-old female adolescent who seeks care after having made her second suicide attempt after 9 months of failed psychological and psychiatric therapy, the standard EMDR protocol is executed in a first unsuccessful session and a variant of the EMDR protocol that occurred incidentally achieving the therapeutic goal. Results: This is an adolescent with a history of failed mental health treatment, the standard intervention protocol with EMDR was executed without success, however; In a second attempt, the patient spontaneously proceeds with desensitization from positive experiences without ever directly addressing the traumatic event. In this case, the reprocessing of the events occurred through positive experiences for the patient instead of what is indicated in the standard protocol where the trauma is reprocessed through the negative event. Conclusion: Psychological treatment using EMDR was effective despite its atypical execution, therefore variations to the original protocol can be applied.